Kinetically Controlled Growth of Phase‐Pure SnS Absorbers for Thin Film Solar Cells: Achieving Efficiency Near 3% with Long‐Term Stability Using an SnS/CdS Heterojunction. Issue 10 (3rd January 2018) - Lim, Dongha; Suh, Hoyoung; Suryawanshi, Mahesh; Song, Gwang Yeom; Cho, Jae Yu; Kim, Jin Hyeok; Jang, Jae Hyuck; Jeon, Chan‐Wook; Cho, Ara; Ahn, SeJin; Heo, Jaeyeong
Abstract: Facile control over the morphology of phase pure tin monosulfide (SnS) thin films, a promising future absorber for thin film solar cells, is enabled by controlling the growth kinetics in vapor transport deposition of congruently evaporated SnS. The pressure during growth is found to be a key factor in modifying the final shape of the SnS grains. The optimized cube‐like SnS shows p‐type with the apparent carrier concentration of ≈10 17 cm −3 with an optical bandgap of 1.32 eV. The dense and flat surface morphology of 1 µm thick SnS combined with the minimization of pinholes directly leads to improved diode quality and increased shunt resistance of the SnS/CdS heterojunction (cell area of 0.30 cm 2 ). An open‐circuit voltage of up to 0.3068 V is achieved, which is independently characterized at the Korea Institute of Energy Research (KIER). Detailed high‐resolution transmission electron microscopy analysis confirms the absence of detrimental secondary phases such as Sn2 S3 or SnS2 in the SnS grains or at intergrain boundaries. The initial efficiency level of 98.5% is maintained even after six months of storage in air, and the final efficiency of the champion SnS/CdS cell, certified at the KIER, is 2.938% with an open‐circuit voltage of 0.2912 V. Abstract : Facile control on morphology of phase pure tin monosulfide (SnS) thin films is enabled by controlling the growth kinetics in vapor transport deposition. Dense and flat surface morphology of cube‐like orthorhombic SnS combined with the minimized pinholes directly leads to improved diode quality and increased shunt resistance of the SnS/CdS heterojunction, achieving the certified efficiency of 2.938%.